Colocation of Entrepreneurs and New Firm Survival: Role of New Firm Founder's Experiential Relatedness to Local Entrepreneurs. (July 2023) - Tavassoli, Sam; Jienwatcharamongkhol, Viroj; Arenius, Pia
Geographical clustering (colocation) influences new firm survival; however, not all new firms within a cluster are impacted equally. In this paper, we elaborate on how the colocation of local entrepreneurs may have different influences on new firm founder's learning depending on his/her fit, in terms of his/her experiential relatedness, to that of local entrepreneurs. We then associate such founder's learning with the higher survival of his/her new firm. We test our hypotheses using a matched founder-firm dataset that covers the population of the knowledge-intensive business service sector in Sweden during 2001–2012. We find support for our propositions concerning the relatedness of new firm founders' experiential background to that of local entrepreneurs. Specifically we find that high level of relatedness to local entrepreneurs enhances the survival rate of a new firm started by a novice founder, whereas intermediate level of relatedness suits better for a new firm started by an experienced founder.